Clinical Assessment and Treatment of the Dysfunctional Larynx after Radiation. Issue 6 (6th September 2013) - Allen, Clint T.; Lee, Chia‐Jung; Merati, Albert L.
Abstract : Objective: To review the pathophysiology of early and late radiation‐related tissue changes, methods to differentiate these changes from disease recurrence, and treatment of these changes in the irradiated larynx. Data Sources: Peer‐reviewed publications. Review Methods: PubMed database search. Conclusions/Implications for Practice: Early and late radiation‐related changes in the larynx manifest variably between individual patients. Severe radiation‐related tissue changes in the larynx and recurrent malignancy share many clinical characteristics, and the presence of malignancy must be considered in these patients. Positron emission tomography may help select patients who need operative biopsy to rule out recurrence. In patients with a cancer‐free but dysfunctional larynx, both surgical and nonsurgical treatment options, including hyperbaric oxygen, are available for attempted salvage. Further investigation is needed before hyperbaric oxygen can be considered standard‐of‐care treatment for these patients.